(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: Describe the practice of health communication and education about diabetes among village health workers in Vu Thu district, Thai Binh province in 2020. Subjects: Village Health Worker and Head of Commune Health Station in the communes of Vu Thu district, Thai Binh province. Method: the epidemiological method described through the cross-sectional investigation, combine quantitative research and qualitative research. Results: 69.5% of village health workers had carried out communication and health education for villagers about diabetes in the past year; Over 80% of village health workers had a plan and over 60% cooperate in communicating and educating about diabetes about diabetes; 15/15 opinion of the head of the station said that the communication and education about diabetes in the commune was small, not continuous, mainly indirect communication; 13/15 comments that the biggest difficulty in health communication and education was that the village health workers were still limited in knowledge and skills.